Anthropometrics of Italian senior male rugby union players: from elite to second division - Fontana, F. Y.; Colosio, A.; De Roia, G. F.; da Lozzo, G.; Pogliaghi, S. (International Journal of Sports Physiology and Performance, 2015)
Anthropometric evaluation of athletes is necessary to optimize talent identification and player development. Objectives: To provide a specific anthropometric reference database of senior male rugby players competing at different levels in the southern European region. Design: Cross-sectional. Methods: In 362 professional players (25 ± 4 y; 138 Italian national team, 97 first-division, and 127 second-division national championships) the authors measured mass, stature, and percentage body fat (plicometry). Mean, SD, and coefficient of variation were calculated for forwards and backs and for positional subgroups. Binomial logistic regression and receiver-operating-characteristic curve were performed to assess which variables best predicted level assignment (international vs national level). Results: For all competitive levels forwards were significantly heavier and taller and had a larger percentage body fat and fat-free mass than backs. The lower the competitive level, the higher the within-role variability observed; furthermore, players in a specific positional subgroup were lighter, shorter, and fatter and had less fat-free mass. Fat-free mass is the variable that best predicts the likelihood of being classified as an international or national player (cutoff value 79.54 kg). Conclusions: The data confirm the specificity in the physical requirements of rugby in individual playing positions at all competitive levels and document significant differences among elite and 1st- and 2nd-division players in the same positional role. These differences may reflect the variable technical abilities, selection, training practices, and requirements of the game among these categories.